Spontaneous acute intussusception in a pregnant woman - Radhouane Achour; Souad Harabi; Khaled Neji (Elsevier, 2017)
Acute intussusception in adults is rare and particularly so in pregnant women. Its incidence ranges from 0.067% to 0.0015% (Choi et al., 2005 Choi et al. (2005) [1]). The non-specific presenting symptoms may be attributed to the pregnancy itself, making the diagnosis difficult. When it happens, however, it causes considerable morbidity and mortality for the pregnant woman and the fetus. In adults, such intussusceptions are mainly secondary to an intestinal disease and frequently a tumor. We present the case of a 21-year-old pregnant woman who was diagnosed of spontaneous acute intussusception at nine weeks of gestation and therapeutic management.